Mathematical modelling: a way of life - Lamon, Susan J.; Parker, Willard A.; Houston, Ken S. (Horwood Pub, 2003)
Mathematical modelling is often spoken of as a way of life, referring to habits of mind and to dependence on the power of mathematics to describe, explain, predict and control real phenomena. This book aims to encourage teachers to provide opportunities for students to model a variety of real phenomena appropriately matched to students' mathematical backgrounds and interests from early stages of mathematical education. Habits, misconceptions, and mindsets about mathematics can present obstacles to university students' acceptance of a ''models-and-modelling perspective'' at this stage of mathematics education. Without prior experience in building, interpreting and applying mathematical models, many students may never come to view and regard modelling as a way of life. The book records presentations at the ICTMA 11 conference held in Milwaukee, Wisconsin in 2003. Examines mathematical modelling as a way of life, referring to habits of mind and dependence on the power of mathematics to describe, explain, predict and control real phenomenaEncourages teachers to provide students with opportunities to model a variety of real phenomena appropriately matched to students' mathematical backgrounds and interests from early stages of mathematical educationRecords presentations at the ICTMA 11 conference held in Milwaukee, Wisconsin in 2003
Proceedings of conference held in Milwaukee, Wisconsin, USA in 2003. - Includes bibliographical references. - Description based on print version record
Keywords: Milwaukee <Wis., 2003>; Electronic books; Congress; Konferenzschrift